Ad fontes : original manuscripts and their significance for studying early Christianity : selected essays - Kraus, Thomas J., 1965- (Texts and editions for New Testament study, 2007)
This selection of essays with autobiographical introduction aims to demonstrate the value of working with the original manuscripts in detail in order to gain a more profound understanding of the many facets of Early Christianity, in particular the texts and background of the New Testament. This book should persuade other scholars to once again take a look at the original manuscripts, whether it be a textual witness to the New Testament, some apocryphal text, a reference to early Christian life, or even a specific socio-historical feature of the life of the common people in the days of early Christianity. The specific selection of essays has been chosen with this purpose in mind, presenting editions of papyri and first-hand information, and showing how to base even complex constructs of ideas on a studious treatment of manuscripts. The essays demonstrate the value of studying manuscripts for lexicography, painting a picture of a socio-historical background, and showing how to assess and evaluate data methodologically.